Reference diffraction patterns, microstructure, and pore-size distribution for the copper (II) benzene-1, 3, 5-tricarboxylate metal organic framework (Cu-BTC) compounds. Issue 1 (22nd December 2014) - Wong-Ng, W.; Kaduk, J.A.; Siderius, D.L.; Allen, A.L.; Espinal, L.; Boyerinas, B.M.; Levin, I.; Suchomel, M.R.; Ilavsky, J.; Li, L.; Williamson, I.; Cockayne, E.; et al.
Abstract : Cu-paddle-wheel-based Cu3 (BTC)2 (nicknamed Cu-BTC, where BTC ≡ benzene 1, 3, 5-tricarboxylate) is a metal organic framework (MOF) compound that adopts a zeolite-like topology. We have determined the pore-size distribution using the Gelb and Gubbins technique, the microstructure using small-angle neutron scattering and (ultra) small-angle X-ray scattering (USAXS) techniques, and X-ray powder diffraction reference patterns for both dehydrated d -Cu-BTC [Cu3 (C9 H3 O6 )2 ] and hydrated h -Cu-BTC [Cu3 (C9 H3 O6 )2 (H2 O)6.96 ] using the Rietveld refinement technique. Both samples were confirmed to be cubic Fm 3 m (no. 225), with lattice parameters of a = 26.279 19(3) Å, V = 18 148.31(6) Å 3 for d -Cu-BTC, and a = 26.3103(11) Å, and V = 18 213(2) Å 3 for h -Cu-BTC. The structure of d -Cu-BTC contains three main pores of which the diameters are approximately, in decreasing order, 12.6, 10.6, and 5.0 Å. The free volume for d -Cu-BTC is approximately (71.85 ± 0.05)% of the total volume and is reduced to approximately (61.33 ± 0.03)% for the h -Cu-BTC structure. The d -Cu-BTC phase undergoes microstructural changes when exposed to moisture in air. The reference X-ray powder patterns for these two materials have been determined for inclusion in the Powder Diffraction File.